Analyzing the Use of Anytime Algorithms on an Unmanned Aerial Vehicle - Becker, L. B.; Raffo, G. V.; Gonçalves, F. S. (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2013)
The use of anytime algorithms (AAs) in real-time systems is not a novelty. Such approach is normally adopted in situations where the WCET of a given task is either unknown or highly pessimistic in comparison with the average execution time. Thereby, AAs provide certain flexibility for stringent real-time applications. In this paper we present the use of AA in a project aimed at designing a small scale Unmanned Aerial Vehicle (UAV). More specifically, the implementation of a subsystem of the UAV as AA is described to proof of concept. By analyzing the results obtained, which are optimistic, it provides the direction to develop the complete control strategy as AA. A preliminary structure of the overall control system under AA is also presented in the paper.